2019
DOI: 10.1108/wje-10-2018-0357
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing FG shells with large deformations and finite rotations

Abstract: Purpose The purpose of this study is dedicated to use an efficient mixed strain finite element approach to develop a three-node triangular shell element. Moreover, large deformation analysis of the functionally graded material shells is the main contribution of this research. These target structures include thin or moderately thick panels. Design/methodology/approach Due to reach these goals, Green–Lagrange strain formulation with respect to small strains and large deformations with finite rotations is used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Xu et al [15] studied the vibration responses and dynamic characteristics of functionally graded cylinders and imperfect microbeams under dynamic harmonic loads. Rezaiee-Pajand and Masoodi [16,17] examined conical beams and columns with a functional classification of the cross-section, verified the effectiveness of the stiffness matrix, and provided an effective calculation unit for the study of functionally graded material shells. Masoodi and Ghandehari [18] studied the dynamic characteristics of functionally graded single-wall carbon nanocoupled curved beams and analyzed the effects of factors such as curvature and interface stiffness on the vibration characteristics of the system.…”
Section: Introductionmentioning
confidence: 91%
“…Xu et al [15] studied the vibration responses and dynamic characteristics of functionally graded cylinders and imperfect microbeams under dynamic harmonic loads. Rezaiee-Pajand and Masoodi [16,17] examined conical beams and columns with a functional classification of the cross-section, verified the effectiveness of the stiffness matrix, and provided an effective calculation unit for the study of functionally graded material shells. Masoodi and Ghandehari [18] studied the dynamic characteristics of functionally graded single-wall carbon nanocoupled curved beams and analyzed the effects of factors such as curvature and interface stiffness on the vibration characteristics of the system.…”
Section: Introductionmentioning
confidence: 91%
“…Their research found out that steel stud walls constructed using conventional detailing have limited blast resistance due to premature buckling instability. A non-linear analysis of FGM sandwich plates and shell, as well as FGM large deformation analysis, is presented in [11][12][13][14]. Similar articles on FGM and resistance of steel wall systems can also be found in several studies [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Mohammad [18] employed a triangular shell element having six nodes to investigate the nonlinear behavior of cylindrical shells with irregular mesh and complicated geometry, where total Lagrangian formulation was utilized considering the large deflection and rotation. Further, Mohammad [19] developed a three-node triangular shell element using a mixed strain finite element approach for nonlinear analysis of FG shells with large deformations and finite rotations. For composite cylindrical shells of given geometry, boundary conditions and material system, the buckling strength is mainly affected by the fiber orientation, stacking sequence and thermal environment [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%